Os sentidos e significados constituídos por alunos do Ensino Fundamental II, a respeito das vivências e saberes deste nível de ensino - Tomé, Maria Carolina Rodrigues (2015)
Due to the small amount of studies published about junior high school, this research intends to contribute to the increase of the understanding of this age group. Through a focal group, a thematic script was debated among six São Paulo public school students, raising questions about the meaning of school, the transition from elementary to junior high school, the relationship between learning and its benefits and challenges, opinion regarding their teachers, colleagues, board of directors and their outlook on life. The data analysis was performed according to a procedure suggested by Aguiar and Ozella (2013) named Nuclei of Meaning: thru the meanings issued by the students about their experiencies and knowledge in junior high, we aimed to reveal more specific areas of meaning. The need for interaction among all the players in the school setting was key as far as the students were concerned; the same can be said about the non-meaning of school, the desired connection by the students between the knowledge they gain and the perspective of life and financial independence, the difficulties in the transition and the lack of a welcoming environment in the process of learning. It becomes evident that this age group deserves great investments in research that support the decision making, specially regarding public policy that may contribute for the management of the classroom by the teacher, of the school by the Principal, bringing meaning to the learning process and to the knowledge shared and built by the teenagers